Community-based aftercare following an emergency department presentation for attempted suicide or high risk for suicide: study protocol for a non-randomised controlled trial - Vida V. Bliokas; Alex R. Hains; Jonathan A. Allan; Luise Lago; Rebecca Sng (BMC, 2019)
Abstract Background Suicide is a major public health issue worldwide. Those who have made a recent suicide attempt are at high risk for dying by suicide in the future, particularly during the period immediately following departure from a hospital emergency department. As such the transition from hospital-based care to the community is an important area of focus in the attempt to reduce suicide rates. There is a need for evaluation studies to test the effectiveness of interventions directed to this stage (termed 'aftercare' interventions). Methods A controlled non-randomised two group (intervention vs treatment-as-usual control) design, using an intention-to-treat model, will evaluate the effectiveness of a suicide prevention aftercare intervention providing follow-up after presentations to a hospital emergency department as a result of a suicide attempt or high risk for suicide. The intervention is a community-based service, utilising two meetings with a mental health clinician and follow-up contacts by peer workers via a combination of face-to-face and telephone for four weeks, with the option of extension to 12 weeks. Seventy-five participants of the intervention service will be recruited to the study and compared to 1265 treatment-as-usual controls. The primary hypotheses are that over 12 months, those who participate in the aftercare follow-up intervention are less likely than controls to present to a hospital emergency department for a repeat suicide attempt or because of high risk for suicide, will have fewer re-presentations during this period and will have lower all-cause mortality. As a secondary aim, the impact of the intervention on suicide risk factors for those who participate in the service will be evaluated using pre- and post-intervention repeated measures of depression, anxiety, stress, hopelessness, belongingness, burdensomeness, and psychological distress. Enrolments into the study commenced on 1 November 2017 and are anticipated to cease in November 2019. Discussion The study aims to contribute to the understanding of effective interventions for individuals who have presented to a hospital emergency department as a result of a suicide attempt or at high risk for suicide and provide evidence in relation to interventions that incorporate peer-workers. Trial registration ACTRN12618001701213. Registered on 16 October 2018. Retrospectively registered.